Culpa debitorului în neexecutarea obligaţiei ca o condiţie de rezoluţiune a contractului [Articol] - Cazac, Octavian (My University, 2012)
Classical contract theory – as promoted by French and Romanian legal doctrine – dictates that the debtor’s fault in the breach of contract is a mandatory condition to the creditor’s right of termination. It supports that, in such a scenario, a party may not terminate the contract, but rather it ends ipso legem. This approach is the product of confusion between the right to damages for breach and the right to terminate, which are completely separate legal remedies. After having analysed the provisions of the Moldovan Civil Code and the trend in the principal European jurisdictions, the CISG as well as the Draft Common Frame of Reference, the author concludes that the classical theory is overly simplistic and ignores the situation of temporary or partial impossibility for which modern legal systems – such as the German or the Italian civil codes – do grant a right of termination. We support that the remedy of termination should be made available to the creditor independent of the debtor’s fault and based solely on the substantial test of fundamental breach of contract or the expiration of an additional period to perform (the German-inspired Nachfrist).